2020
DOI: 10.3390/agronomy10081158
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Valorisation of Biowaste for Soilless Cultivation of Salvia Officinalis in a Circular Bioeconomy

Abstract: The aim of this work is to assess the usefulness of biowaste deriving from Circular Bioeconomy (CBE) processes (i.e., vermicompost, compost and digestate), as growing substrates for the partial or total replacement of peat, by measuring the vegetation biometric parameters of sage (Salvia officinalis L.)—leaf area; Soil Plant Analysis Development (SPAD) value (index of chlorophyll concentration); fresh and dry weight of leaves; stem weight; root length. The results showed that vermicompost positively influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This harsh environment can cause osmotic stress and ultimately lower productivity of plants. A previous study investigating the use of the solid portion of digestates as an alternative to peat for greenhouse production found reduced plant growth in Salvia oficianalis grown in mixtures of digestate and peat, as compared with peat alone [38]. A more recent study found a high EC and high plant tissue content of Na + under digestate treatments, similar to findings from this study with the use of liquid digestates [39].…”
Section: Plant Growth and Salinitysupporting
confidence: 86%
“…This harsh environment can cause osmotic stress and ultimately lower productivity of plants. A previous study investigating the use of the solid portion of digestates as an alternative to peat for greenhouse production found reduced plant growth in Salvia oficianalis grown in mixtures of digestate and peat, as compared with peat alone [38]. A more recent study found a high EC and high plant tissue content of Na + under digestate treatments, similar to findings from this study with the use of liquid digestates [39].…”
Section: Plant Growth and Salinitysupporting
confidence: 86%
“…Chakraborty et al (2019) [103] throw light on the hitherto-overlooked immense potential for generating biomethane and biohydrogen by co-digesting the huge quantities of food and vegetable wastes generated in India, all along the value chain, especially on the downstream, from restaurants and public eateries, while Sharma et al (2019) [274] support vermicomposting (symbiosis between earthworms and microorganisms) as an effective, economical and environment-friendly approach when the purpose is simply to produce rich organic fertilisers. Vermicompost has been shown to be a better alternative than compost and digestate, as a replacement for peat, for the soilless cultivation of the perennial evergreen Salvia officinalis (sage, in common parlance) [67]. Dealing with wastes from tomato, orange, potato and olive processing units in Italy, the techno-economic analysis in Cristobal et al (2018) [127] shows that it is usually economically more attractive to centralise the bio-refining by concentrating the production of the valorised bio-products and availing of economies of scale, albeit necessitating transportation of the feedstocks over longer distances.…”
Section: Municipal and Industrial Solid Waste And Sewage Managementmentioning
confidence: 99%
“…The total K 2 O content of the soil is significantly correlated to the % amount of mono-, sesqui-, and diterpenes of essential oil [15]. According to several papers, the sage yield was improved by nutrient supply with compost, manure, fertilizers, or soil amendments [19][20][21][22][23][24][25][26][27][28]. Mona et al (2008) published that the fertilization by 14.3 m 3 /ha compost (1.40:0.47:1.21 = N:P:K, where 263 mg NH 4 NO 3 is in 1 kg compost) caused better yield than the application of mineral fertilizers [28].…”
Section: Introductionmentioning
confidence: 99%